2!/7(1,4а-3 1/2б) -1,2(5/6а-0,5б) =-0,2(3а-2б)
2/7(1 2/5а-3 1/2б) -1 1/5(5/6-1/2)=
2/7*1 2/5а-2/7*3 1/2б-1 1/5а+1 1/5*1/2=
=2/5а-б-а+3/5б=-3/5а-2/5б=-0,6а-0,4б=--0,2(3а-2б)
ответ:2!/7(1,4а-3 1/2б) -1,2(5/6а-0,5б) =-0,2(3а-2б)
вот и всё тут нет ничего трудного
2!/7(1,4а-3 1/2б) -1,2(5/6а-0,5б) =-0,2(3а-2б)
2/7(1 2/5а-3 1/2б) -1 1/5(5/6-1/2)=
2/7*1 2/5а-2/7*3 1/2б-1 1/5а+1 1/5*1/2=
=2/5а-б-а+3/5б=-3/5а-2/5б=-0,6а-0,4б=--0,2(3а-2б)
ответ:2!/7(1,4а-3 1/2б) -1,2(5/6а-0,5б) =-0,2(3а-2б)
2/7(1 2/5а-3 1/2б) -1 1/5(5/6-1/2)=
2/7*1 2/5а-2/7*3 1/2б-1 1/5а+1 1/5*1/2=
=2/5а-б-а+3/5б=-3/5а-2/5б=-0,6а-0,4б=--0,2(3а-2б)
вот и всё тут нет ничего трудного